Determination of serum lipid profile in patients with diabetic macular edema that referred to Shahid Beheshti and Ayatollah Rouhani Hospitals, Babol during 2011-2012 - Seyed Ahmad Rasoulinejad; Habib-ollah Iri (Babol University of Medical Sciences, 2015)
Background: Diabetes is a common metabolic disorder leading to the development of many complications, among which diabetic retinopathy and macular edema are the most significant. These complications can contribute to blindness if not diagnosed or treated properly, and several studies have been conducted to evaluate the methods for the prevention or slowing down their progression. Therefore, serum lipids, apparently play an effective role in the creation and acceleration of macular edema, we therefore determined the relationship of serum lipid level in patients with diabetic macular edema in the present study. Methods: 180 participants were selected from patients with the definite diagnosis of diabetes referred to the eye clinic of Shahid Beheshti and Ayatollah Rouhani Hospitals of Babol during 2011-2012, the patients with a history of taking lipid -lowering drugs and hypertension were excluded from the study. The study data were provided from the medical records of each patients. SPSS Version 18 was used for analyses. Results: In the present investigation, the mean age of participants was 53.22±with the age range of 18-77 years. Ninety patients with diabetic retinopathy and macular edema were compared with ninety patients with diabetic retinopathy without macular edema (control group) were compared. There was a significant difference in serum cholesterol and LDL-cholesterol between patients and groups (p<0.000). Conclusion: The results of this study indicate that high serum cholesterol and LDL-cholesterol is associated with severity of diabetic retinopathy particularly with macular edema